2022
DOI: 10.1093/mnras/stac768
|View full text |Cite
|
Sign up to set email alerts
|

Large-amplitude periodic outbursts and long-period variables in the VVV VIRAC2-β data base

Abstract: The VISTA Variables in the Via Lactea (VVV) survey obtained near-infrared photometry toward the Galactic bulge and the southern disc plane for a decade (2010 – 2019). We designed a modified Lomb-Scargle method to search for large-amplitude ($\Delta K_{s, 2{{\ \rm per\ cent}}-98{{\ \rm per\ cent}}}$ > 1.5 mag) mid to long-term periodic variables (P>10 d) in the 2nd version of VVV Infrared Astrometric Catalogue (VIRAC2-β). In total, 1520 periodic sources were discovered, including 59 candidate peri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 92 publications
1
10
0
Order By: Relevance
“…Our cuts on Wesenheit magnitude have sought to eliminate these intrinsically dimmer contaminants. We have checked whether any of our objects are in the young stellar object catalogues of Guo et al (2021) and Guo et al (2022). One source in our catalogue (VIRAC Mira 68) has been identified by Guo et al (2022, VVV_PB_122) as a potential periodic outbursting young stellar object.…”
Section: The Sample Selection Functionmentioning
confidence: 95%
See 2 more Smart Citations
“…Our cuts on Wesenheit magnitude have sought to eliminate these intrinsically dimmer contaminants. We have checked whether any of our objects are in the young stellar object catalogues of Guo et al (2021) and Guo et al (2022). One source in our catalogue (VIRAC Mira 68) has been identified by Guo et al (2022, VVV_PB_122) as a potential periodic outbursting young stellar object.…”
Section: The Sample Selection Functionmentioning
confidence: 95%
“…We also employ a number of cuts that remove a further ∼ 40 per cent of the sample. Contaminants include young stellar objects (YSOs, see Guo et al 2022), other fainter giant stars and blended photometry not properly handled in our calibration step. We have found that a small fraction of aliases that appear around 1 year period also 3 Using the Akaike or Bayesian information criteria instead results in minor differences in the final sample.…”
Section: Mira Variable Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variability in the MIR on timescales of days to months has been observed for many YSOs (e.g., Rebull et al 2014;Park et al 2021), though a wide range of phenomena besides accretion variability can be responsible (e.g., rotating disk warps and starspots). Several notable examples show variability attributed to periodic accretion instabilities (L1634 IRS 7; Hodapp & Chini 2015; V347 Aurigae; Dahm & Hillenbrand 2020; see also Guo et al 2022), pulsed accretion from interaction with a binary (L1527 IRS; Cook et al 2019), or rotation of a warped inner disk (LRLL 54361; Muzerolle et al 2013). Investigating such sources with higher-cadence and higher-resolution submillimeter/millimeter observations is thus important for identifying the nature and distribution of rapid accretion variability in protostars.…”
Section: Constraining Envelope Models and Accretion Burst Propertiesmentioning
confidence: 99%
“…In general, bursts are related with aperiodic behaviour of flux changes due to variable accretion and they can last from days to months, although they can also have durations of hours (Hillenbrand & Findeisen 2015;Cody et al 2014). However, there has been evidence of periodic outbursts due to accretion, when the latter is regulated by the presence of a low-mass companion (Dunhill et al 2015;Teyssandier & Lai 2020;Guo et al 2022). Most importantly, accretion processes will leave a signature in optical and infrared light curves that, depending on the view angle or the location of the spot, could be well correlated.…”
Section: Introductionmentioning
confidence: 99%